Excel as an optimization tool applied to multicomponent distillation column sizing - Luan Jonas de Souza Ribeiro; Camila Rodrigues Carneiro; Sara Gallegos Bosmediano; Mateus Tomaz Neves; Manoela Maciel dos Santos Dias; Fernanda Raquel Carvalho (The Journal of Engineering and Exact Sciences)
The unit operation of distillation is a method of significant importance for industrial separation processes, as it enables the fractionation of a mixture based on the differences in volatility among its components. Considering that a typical initial mixture generally contains three or more products of interest, studies aimed at optimizing multicomponent distillation, although scarce in the literature, are increasingly imperative to ensure efficiency and reduce operational and energy costs associated with the process. Since sizing multicomponent distillation columns using the Fenske-Underwood and Gilliland (FUG) and Kirkbride methods involves extensive and complex calculations to obtain operational parameters, the objective of this study was to develop a computational method using Microsoft Excel® software to make them more practical and enhance the accuracy of the results obtained. The functionality of the developed spreadsheet was verified through the resolution of an example of application, both manually and electronically. In both cases, the results obtained were identical, but with significantly lower time consumption and probability of error by the electronic method, demonstrating its potential for use in academic and industrial settings.